SANITARY AND MICROBIOLOGICAL ASSESSMENT OF COLD AND HOT MINERAL SPRINGS OF PRIBAIKALYE - D. D. Barkhutova; B. V. Darmayeva; B. B. Namsarayev (Acta Biomedica Scientifica, 2012)
Studying of distribution and number of indicator microorganisms has allowed to estimate springs water quality by microbiological indicators. The koliformal bacteria have been found in water and. ground precipitation of hot and. cold springs. Opportunistic microorganisms have been allocated - Enterobacter aewgenes, Klebsiella oxytoka, Escherichia coli, Enterobacter agglomerans, Enterobacter cloacae, Enterobacter amnigenus (biogroup 2), Citrobacter Freundi.